Book Review: Jus Cogens â International Law and Social Contract - Handayani, Irawati (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2016)
This book is based on the doctoral thesis completed by the author as an International Scholar of the Cambridge Overseas Trust at the University of Cambridge. The main idea of the books lies on the fact that jus cogens still become one of the most complex doctrines in contemporary international law. The legal foundation of jus cogens is still questionable, whether it lies on natural law, positive law or even to higher or divine origin. However, there is general agreement that jus cogens represent the fundamental value in international society or so-called higher norm in international law.Â DOI: https://doi.org/10.22304/pjih.v3n3.a11